2019
DOI: 10.1016/j.clnu.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of nutrition support during extracorporeal membrane oxygenation

Abstract: Adequate energy and protein delivery during vv-ECMO is possible but underfeeding is still common, especially in those who are more severely ill or who have more severe organ dysfunction. Patients with inadequate energy or protein delivery did not differ in ICU and 6-month survival. Prospective studies investigating optimal feeding in this patient cohort are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
0
47

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(138 citation statements)
references
References 31 publications
4
69
0
47
Order By: Relevance
“…10,11 A recently published retrospective study by MacGowan et al investigated the association between nutrition delivery and outcomes in patients on VV ECMO at a single center and found that patients who received optimal nutrition, defined as 80%-110% of their nutrition prescription, experienced longer stays on VV ECMO. 22 These findings draw attention to the potential consequences of applying recommendations for general critical illness to patients who require VV ECMO. Additionally, the authors noted that they provided less protein than the 2016 ASPEN/SCCM guidelines recommended, which may impact outcomes if insufficient protein is provided to support metabolic processes during critical illness.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…10,11 A recently published retrospective study by MacGowan et al investigated the association between nutrition delivery and outcomes in patients on VV ECMO at a single center and found that patients who received optimal nutrition, defined as 80%-110% of their nutrition prescription, experienced longer stays on VV ECMO. 22 These findings draw attention to the potential consequences of applying recommendations for general critical illness to patients who require VV ECMO. Additionally, the authors noted that they provided less protein than the 2016 ASPEN/SCCM guidelines recommended, which may impact outcomes if insufficient protein is provided to support metabolic processes during critical illness.…”
Section: Discussionmentioning
confidence: 97%
“…These findings draw attention to the potential consequences of applying recommendations for general critical illness to patients who require VV ECMO. Additionally, the authors noted that they provided less protein than the 2016 ASPEN/SCCM guidelines recommended, which may impact outcomes if insufficient protein is provided to support metabolic processes during critical illness …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven observational studies were found describing nutrition practices in patients receiving ECMO (both VV and VA) . In these studies (Table ), EN was most frequently commenced within 24 hours of starting ECMO, with several studies reporting a mean or median time to feeding of around 13 hours.…”
Section: Timing and Route Of Nutrition Supportmentioning
confidence: 99%
“…In these studies (Table ), EN was most frequently commenced within 24 hours of starting ECMO, with several studies reporting a mean or median time to feeding of around 13 hours. In the largest study, 96% of patients were fed within 24 hours. The reporting of adverse events is rare and likely to be impacted on by the predominantly retrospective nature of the studies, but in a prospective multicenter observational study of 107 patients, 5 patients (4.5%) were reported to have bowel ischemia .…”
Section: Timing and Route Of Nutrition Supportmentioning
confidence: 99%